Pengembangan Media Dongeng Anak Muatan Kearifan Lokal Berbasis Macromedia Flash Bagi Siswa Sekolah Dasar - Anafiah, Siti; Purnama Sari, Dyan Indah (Wahana Sekolah Dasar, 2022)
Describe the development and feasibility of children's fairy tale media containing local wisdom based on macromedia flash for elementary school students. This type of research is RnD. This research procedure includes potential problems, planning, design development, product validation, product revision. This design validation was carried out by material experts and media experts. Data analysis used content analysis and descriptive percentage analysis. The results showed that animation design, material design, operation, benefits, presentation of material, and impact on readers. Material experts judge from things related to the material in the media, while media experts judge from things related to the appearance and operation of macromedia flash fairy tales and the role of media in learning. Children's fairy tales get a positive response from the listeners, namely children and can develop reading and speaking skills.